Study on Using Multimodal Analgesia in Postoperative Cardiac ICU (KYAMC Journal, 2022)
Background: The cardiac operative procedure has a significant relationship with acute onset of pain. After cardiac surgery, pain has been managed with the help of opiate analgesics.Objective: To analyze the adverse effects of postoperative multimodal analgesia after cardiac surgery concerning the physical and specific biochemical parameters of undergoing surgery patients.Materials & Methods: It was a single-center, prospective study where patients were approached on the day before their cardiac surgery. A total of 120 post-cardiac operative surgery patients at Khwaja Yunus Ali Medical College Hospital, Sirajganj were included for this study purpose.Results: In first group, three types of analgesia were used in 60 patients and in second group, five types of analgesia were used in another 60 patients. About 76.7% were male and mean age was 45.73 (± 11.3) years. Fentanyl was used for all patients followed by paracetamol (96.7%), diclofenac (83.3%), tramadol (16.7%), and pethidine (3.3%). Drug-induced nausea and vomiting were found in 76.7%and 66.7% patients respectively followed by drowsiness (36.7%) and vertigo (20.0%).Conclusion: In patients undergoing cardiac surgery, a multimodal regimen offered better analgesia. Furthermore, nausea and vomiting complaints were reduced significantly in the multimodal group.KYAMC Journal Vol. 13, No. 02, July 2022: 94-97